2021
DOI: 10.2147/jmdh.s319553
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Nutritional Factors Influencing the Duration of Mechanical Ventilation Among Adult Patients with Critical Illnesses in an Intensive Care Unit

Abstract: Objective This study aims to identify the impact of nutritional factors on mechanical ventilation duration for critical patients. Patients and Methods The current study was a single-center, prospective observational design which enrolled one-hundred critically ill patients who were admitted to an intensive care unit (ICU). It demonstrates purposive sampling and also performs the descriptive nutritional factors influencing the mechanical ventilation duration. Daily calor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The results showed that the most important barrier was "Delay in physician ordering initiation of enteral nutrition" [3.33 ±1.32, 3 (2-5)]which was included in the "delivery of EN" domain. The mean score of this item as indicated by the dietitians was [3.9 ±1.4, 5 (3)(4)(5)], by physicians was [3.09 ±1.1, 3 (2-4)] and by nurses was [3.06 ±1.3, 3 (2-4)]. The second most important barrier was "Waiting for the dietitian to assess the patients" [3.22 ±1.2, 3 (2-4)] which was included in the "dietitian support" domain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the most important barrier was "Delay in physician ordering initiation of enteral nutrition" [3.33 ±1.32, 3 (2-5)]which was included in the "delivery of EN" domain. The mean score of this item as indicated by the dietitians was [3.9 ±1.4, 5 (3)(4)(5)], by physicians was [3.09 ±1.1, 3 (2-4)] and by nurses was [3.06 ±1.3, 3 (2-4)]. The second most important barrier was "Waiting for the dietitian to assess the patients" [3.22 ±1.2, 3 (2-4)] which was included in the "dietitian support" domain.…”
Section: Resultsmentioning
confidence: 99%
“…The second most important barrier was "Waiting for the dietitian to assess the patients" [3.22 ±1.2, 3 (2-4)] which was included in the "dietitian support" domain. The mean score of this item as indicated by the dietitians was [3.5 ±1.4, 4 (2-5)], by physicians was [3.2 ±1.1, 3 (2-4)] and by nurses was [2.79 ±1.1, 3 (2)(3)]. The least important barriers were "Non-ICU physicians requesting patients not be fed enterally" [3.01 ±1.2, 3 (2-4)] preceded by "General belief among ICU team that provision of adequate nutrition does not impact on patient outcome" [3.03 ±1.3, 3 (2-4)]; both barriers were included in the "critical care providers attitude and behaviour" domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this guidance is universally recommended unless there are specific exceptions, such as uncontrolled haemodynamic compromise, profound hypoxia, uncontrolled gastro-intestinal bleeding and/or abdominal compartment syndrome [9]. There is demonstrable benefit from optimised nutritional status, time to initial enteral nutrition and meeting calorie target requirements within 7 days of admission, with a significant reduction in time spent undergoing mechanical ventilation if these three factors are optimally achieved [10 ▪ ]. However, early initiation of enteral nutrition has been associated with gastrointestinal intolerance and vomiting in 30–70% of patients in critical care, as well as gut ischemia in critically ill patients with shock [11,12].…”
Section: Enteral Feeding Tube Placement: Gastric Versus Postpyloricmentioning
confidence: 99%
“…These indices are widely used to assess nutrition in patients with malignancies [ 7 , 8 ], stroke [ 9 , 10 ], and sepsis [ 11 ]. Moreover, early nutrition status is associated with the duration of mechanical ventilation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%